Media advocacy in catalyzing actions by decision-makers: case study of the advance family planning initiative in Kenya - Choge, Irene; Mwalimu, Rammah; Mulyanga, Sam; Njiri, Sally; Kwachi, Beatrice; Ontiri, Susan (Frontiers in Global Women's Health, 2023)
Media can play a critical role in informing and educating the public on health issues. A paradigm shift is occurring in the development sector as the use of media engagement for advocacy on public health issues increases. In Kenya, Advance Family Planning (AFP) initiative used this approach to further the country’s progress in achieving family planning goals. This case study documents AFP experience in supporting media to engage leaders and decision-makers on the need to unlock bureaucratic bottlenecks that limit success of family planning services. AFP’s media efforts added weight to the work of advocates who push for increased political commitments and investments in family planning. Media advocacy efforts helped catalyze actions by decision-makers across Kenya—focusing on strengthening accessibility and availability of contraceptive methods and fast-tracking implementation of policy actions to address adolescent pregnancy. Media advocacy efforts contributed to advancing family planning initiatives in the country. Media advocacy should be a key pillar of family planning programs and of other sectors.